The Impact of Regional Liberalization And Harmonization In Road Transport Services : A Focus On Zambia And Lessons For Landlocked Countries - Raballand, Gael (The World Bank, 2008)
Based on a detailed empirical study, this paper argues that regional liberalization of trucking services has had an important effect on transport costs and tariffs for Zambia's economy. Zambia is a peculiar example in Southern Africa as it benefits from relatively low transport costs compared with other landlocked countries in Africa. This is mainly because of competition between Zambian and other regional, mainly South African, operators and because of South African investments in Zambia's trucking industry. As a result, the costs of operators registered in Zambia and South Africa are similar. The study also demonstrates that enhancing trucking interoperability in Southern Africa would significantly impact positively the Zambian trucking industry's competitiveness. The main measures to significantly increase trucking competitiveness in the region would more likely derive from reducing fuel costs in Zambia, improving border-post operations, and relaxing South African truck import rules